Innate immune receptors drive dengue virus immune activation and disease - Sprokholt, Joris (Future Virol, 2017)
Dengue is a worldwide disease with 400 million annual infections that can lead to septic shock and viral hemorrhagic fever with internal bleeding. These symptoms are the result of uncontrolled immune activation. Macrophages and dendritic cells are the main target of dengue virus (DENV) and the cellular source of cytokines associated with this immune activation. Macrophages and dendritic cells express several innate immune receptors that have been implicated in DENV immune activation, of which, CLEC5A, RIG-I and MDA5 are most important. Notably, activation of these receptors have profound effects on adaptive immune responses against DENV. This review will focus on how innate immune receptors drive DENV immune activation by inducing inflammatory cytokines and by activating adaptive immune responses.